Open water - Kentis, Chris; Ryan, Blanchard, 1967-; Travis, Daniel, 1968-; Stein, Saul.; Lau, Estelle, 1967-; Williamson, Michael; Lau, Laura, 1964-; Revell, Graeme; Lions Gate Home Entertainment (Santa Monica, Calif. : Lions Gate Home Entertainment, 2004)
Susan and Daniel are a happily married couple who are taking a much needed vacation to the islands. They are hoping for a memorable trip. However, their vacation turns tragic when their scuba diving party leaves them in the middle of the ocean by the careless diving boat crew. As the reality of isolation sets in, they turn to one another for support. Unable to flag down passing boats, they begin to panic as encircling sharks begin to appear.
Directors of photography, Chris Kentis, Laura Lau ; music, Graeme Revell.
Blanchard Ryan, Daniel Travis, Saul Stein, Estelle Lau, Michael Williamson, Cristina Zenaro, Jon Charles.
MPAA rating: R; for language and some nudity.
DVD, region 1, widescreen (16:9) presentation; Dolby Digital 5.1 surround, DTS 6.1 sound.
Closed-captioned.
Keywords: Married people -- Drama; Scuba divers -- Drama; Sharks -- Drama; Video recordings for the hearing impaired; Feature films; Thriller -- Feature